Microfilaria in fine needle aspiration smears of neoplastic lesions: a case series - Dr. Rita Yadav; Dr. Mala Sagar; Dr. Malti Kumari Maurya; Dr. AA Sonkar; Dr. Ashutosh Kumar (Tropical Journal of Pathology and Microbiology, 1970)
Filariasis is a major public health problem in south East Asia including India. It is transmitted by bite of culex mosquito and most commonly caused by Wauchereria bancrofti. Conventional mode of diagnosis is demonstration of microfilaria in peripheral blood smear and body fluid. Co-existence of microfilaria with neoplastic lesions are rare. We present herewith 5 interesting cases of neoplastic lesions where microfilaria were coexistent with one case each of non Hodgkin lymphoma, metastatic adenocarcinoma of supraclavicular lymph node, metastatic adenocarcinoma of cervical lymph node, Infiltrating ductal carcinoma of breast, benign phylloides tumor of breast.